2017
DOI: 10.1002/marc.201700055
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Sensing Achieved by GaAs Nanowires and oCVD Polymer Coating

Abstract: Novel structures comprised of GaAs nanowire arrays conformally coated with conducting polymers (poly(3,4-ethylenedioxythiophene) (PEDOT) or poly(3,4-ethylenedioxythiophene-co-3-thiophene acetic acid) display both sensitivity and selectivity to a variety of volatile organic chemicals. A key feature is room temperature operation, so that neither a heater nor the power it would consume, is required. It is a distinct difference from traditional metal oxide sensors, which typically require elevated operational temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…38 This approach relies on the oxidative chemical vapour deposition (oCVD) 39,40 reaction of porphyrins with free meso and b positions using a suitable volatile oxidant (preferentially FeCl 3 ) for dehydrogenative coupling. The oCVD technique is been mainly used for the synthesis of poly(3,4ethylenedioxythiophene) (PEDOT) [41][42][43] and polyaniline (PANI) 44 nding application in organic electronics, 45 volatile compound detectors [46][47][48] and supercapacitors. 49,50 Furthermore, the oxidant acts as doping agent directly yielding conductive thin lms on virtually any substrates including sensitive substrates such as paper and polymers.…”
Section: Introductionmentioning
confidence: 99%
“…38 This approach relies on the oxidative chemical vapour deposition (oCVD) 39,40 reaction of porphyrins with free meso and b positions using a suitable volatile oxidant (preferentially FeCl 3 ) for dehydrogenative coupling. The oCVD technique is been mainly used for the synthesis of poly(3,4ethylenedioxythiophene) (PEDOT) [41][42][43] and polyaniline (PANI) 44 nding application in organic electronics, 45 volatile compound detectors [46][47][48] and supercapacitors. 49,50 Furthermore, the oxidant acts as doping agent directly yielding conductive thin lms on virtually any substrates including sensitive substrates such as paper and polymers.…”
Section: Introductionmentioning
confidence: 99%
“…PS coating has demonstrated to improve the selectivity for n ‐pentane over methanol and toluene by 2.7‐ and 4.4‐fold, respectively, and such as device exhibited the high signal quality of ≈30 dB and short response time of ≈400 s . Wang et al demonstrated the similar hybrid sensing device using GaAs nanowires arrays instead of VA‐CNT which exhibited good sensitivity toward many organic vapor analytes. The hybrid sensing device based on oCVD CPs combines the merits of both kinds of sensors and has the advantages such as: nonpolar molecule detection at room temperature, high signal quality, good reversibility, and short response time, and retaining high surface area morphology of VA‐CNTs by the oCVD dry method.…”
Section: Devices On Nanostructured Surfacesmentioning
confidence: 99%
“…The conjugated polymer is then synthesized through gas phase injection of 3,4-ethylenedioxythiophene (EDOT) as monomer and one oxidant. Further, the solid oxidant iron trichloride (FeCl 3 ) was the first and most common one to be studied, ,, , although in recent years, liquid oxidants, namely, 3-thiophene acetic acid (TAA), vanadium oxytrichloride (VOCl 3 ), sulfuric acide (H 2 SO 4 ), bromine (Br 2 ), molybdenum­(V) chloride (MoCl 5 ), copper­(II) chloride (CuCl 2 ), and antimony pentachloride (SbCl 5 ), , have replaced it with the aim of optimizing the performance of PEDOT and avoiding sublimation drawbacks. Among these candidates, SbCl 5 has recently emerged as one of the most commonly used precursors due to its low toxicity, high volatility, and cost-effectiveness compared to other compounds such as molybdenum­(V) chloride (MoCl 5 ) or vanadium oxytrichloride (VOCl 3 ) .…”
Section: Introductionmentioning
confidence: 99%